Cell lineage specification at single cell resolution - Yang, Jian; Liu, Pentao (Stem Cell Investigation; Vol 4, No 9 (September 2017): Stem Cell Investigation, 2017)
Single cell technology has been widely used in developmental and stem cell biology. In mouse, single cell transcriptome has revealed the cell lineage specification in pre-implantation and post-implantation stages embryo. Now Mohammed et al. investigated the dynamic cell fate commitment during the transition from peri-implantation to early post-implantation stage with single cell RNA sequencing. Except confirmation of some previous findings, the time window and cell subclusters of cell specification are more precisely determined, along with possible new mechanism for X chromosome re-activation and inactivation in female embryo and for exit from pluripotency and lineage commitment. These data will not only fill the missing link in mouse embryo development, but provide insights into embryo development of other mammalian species including human.